Central African Economic and Monetary Community (CEMAC) : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses the CEMAC Regional convergence framework that aims at ensuring that national policies are consistent with a smooth functioning of CEMAC's economic and monetary union. Established in 1999, a few years after the 1994 devaluation, as part of the Convergence and Stability Pact, it aims at addressing the coordination challenges posed by CEMAC's common monetary policies and decentralized fiscal policies. CEMAC Regional convergence framework aims at ensuring that national policies are consistent with a smooth functioning of CEMAC's economic and monetary union. Established in 1999, a few years after the 1994 devaluation, as part of the Convergence and Stability Pact, it aims at addressing the coordination challenges posed by CEMAC's common monetary policies and decentralized fiscal policies. Owing in part to the weaknesses, the fiscal convergence framework has not been sufficient to prevent a sharp deterioration in public accounts over the last few years.